Sistem Informasi Geografis Untuk Identifikasi Awal Tingkat Kerentanan Pencemaran Pada Lokasi Fasilitas Penampungan Produk Minyak Dan Gas Bumi - Indah Crystiana; Taufan Junaedi (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2022)
Construction of oil and gas product storage facilities is one of the oil and gas activities in the downstream sector. A common impact on the environment from oil and gas activities is in the form of pollution of land, water, or air, it is necessary to identify the level of vulnerability to pollution early, areas that are sensitive to pollution are the main concern. The results of the initial identification of the level of vulnerability to pollution are shown in the map of the level of vulnerability to pollution processed using a geographic information system using the method of interpolation, weighting, and overlapping. The results of the initial identification of the level of vulnerability to pollution at the location of the oil and gas product storage facilities are divided into 3 (three) classes of vulnerability levels, low, medium, and high. The study area is in a relatively medium to high level of vulnerability with a high level of vulnerability being near the sea, so it needs high attention in its management.